Confronting the Duality of Unemployment and Education: Breaking the Cycle of Poverty in West Kalimantan - Alma Putri; Fanny Rahmasari; Fransiskus Fran (Jurnal Forum Analisis Statistik, 2023)
Poverty is one of the obstacles to the progress of a region/country. West Kalimantan is one of the areas in Indonesia that faces challenges in reducing destitution. Therefore, this study intends to analyze the impact of the unemployment rate and education level on the poverty rate in the West Kalimantan Area. The strategy applied in this study is board information relapse analysis, which combines time series data for six years (2017-2022) and cross-area information from 14 regencies/cities in West Kalimantan Area. In this consideration, a random impacts model was used and the regression equation Y=4.71-0.37X_1+0.03X_2 was found. The results indicate that the education level contains a negative and critical influence on the poverty rate. In contrast, the unemployment rate incorporates a positive and critical impact on the poverty rate.